2018
DOI: 10.1038/s41598-018-27945-6
|View full text |Cite
|
Sign up to set email alerts
|

Electron heating in rf capacitive discharges at atmospheric-to-subatmospheric pressures

Abstract: Electron heating is a fundamental and multidisciplinary phenomenon in partially ionized gases, from the planet’s ionosphere to laboratory-scale plasmas. Plasmas produced at ambient or reduced pressures have recently shown potential for scientific and industrial applications. However, electron heating, which is strongly coupled to the physicochemical properties of these plasmas, has been poorly understood. We experimentally found the rapid structural transition from non-local to local electron heating in collis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…T e shown in figure 2(b) displays a similar evolution as that of the line intensity in figure 2(a) (brief maxima near the cathode). This behaviour is similar to the one reported in [21]. The time lag of about 10 ns between the emission (a) and the electron temper ature (b) is coherent with the time lag between electron heating and ionization in typical capacitive discharges [13].…”
Section: Resultssupporting
confidence: 87%
“…T e shown in figure 2(b) displays a similar evolution as that of the line intensity in figure 2(a) (brief maxima near the cathode). This behaviour is similar to the one reported in [21]. The time lag of about 10 ns between the emission (a) and the electron temper ature (b) is coherent with the time lag between electron heating and ionization in typical capacitive discharges [13].…”
Section: Resultssupporting
confidence: 87%
“…First, most interference Figure 5. Optical emission spectroscopy results of rf capacitive discharges at atmospheric pressure [177]. Raw optical emission spectra of (a) helium and (b) argon rf capacitive discharges in the spectral range of 250-850 nm.…”
Section: Imaging Techniques (2-d)mentioning
confidence: 99%
“…ICCD cameras, which have high sensitivity and high gating speed, enable nanosecond-and rf phase-resolved electron characterization in conjunction with optical filters or spectrometers. In this review, we leave practical issues and considerations related to ICCD cameras, which can be easily found in earlier articles [177,178]. Park et al [177] first proposed and reported a 2-D rf phase-resolved electron characterization using a combination of an ICCD camera and optical filters in argon rf capacitive discharges at atmospheric Figure 6.…”
Section: Imaging Techniques (2-d)mentioning
confidence: 99%
See 2 more Smart Citations